Promoting Behaviors of Students against Health Hazards Caused by Industrial Pollution in High Schools in Indonesia - Nakagawa, Ami (Angstrom Centre of Education, 2024)
Industrial pollution is a severe problem in Indonesia, and it has a huge impact on achieving a sustainable society. Nevertheless, Indonesian students are not well prepared to protect themselves from it. This study aims to clarify the extent to which Indonesian school education can contribute to the transformation of behaviors against industrial pollution health hazards. This study analyzes school curriculum and textbooks in Indonesia to investigate whether the curriculum and textbooks affect students’ behaviors against industrial pollution health hazards. The results show that the knowledge aspect was better complemented than expected. However, there is a lack of systematic investigation, which is a challenge for improving students’ behaviors against industrial pollution health hazards. This study shows that once the lack of systematic investigation is overcome, Indonesian curriculum and textbooks could become an excellent medium to contribute to students’ behaviors against industrial pollution health hazards, thus securing their health rights.